2016
DOI: 10.1177/1938640016666914
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Physiological Gait Pattern in Children Without the Influence of Footwear

Abstract: Diagnostic, Level IV: Case series.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 6 publications
1
3
0
Order By: Relevance
“…Previous studies reported that children habitually barefoot had longer, wider feet and higher arches than children habitually shod [6,[9][10][11]59,60]. Additionally, there was also a link between shoe-wearing age and the incidence of flat feet, with individuals starting shoe-wearing earlier in childhood presenting lower arch heights and higher percentage of flatfoot [61][62][63]. These studies provide more confirmation that regions, ethnicities, climate, and shoe habits will affect children's foot development [9][10][11]29,[57][58][59][60].…”
Section: Children's Footwear Effect On Footsupporting
confidence: 53%
See 1 more Smart Citation
“…Previous studies reported that children habitually barefoot had longer, wider feet and higher arches than children habitually shod [6,[9][10][11]59,60]. Additionally, there was also a link between shoe-wearing age and the incidence of flat feet, with individuals starting shoe-wearing earlier in childhood presenting lower arch heights and higher percentage of flatfoot [61][62][63]. These studies provide more confirmation that regions, ethnicities, climate, and shoe habits will affect children's foot development [9][10][11]29,[57][58][59][60].…”
Section: Children's Footwear Effect On Footsupporting
confidence: 53%
“…Studies found that there are gait changes between children aged 6-7 years and children aged 10-11 years. After 11 years old, gait becomes stable, showing similarity to adults [63]. An updated literature review study may assist in determining the effect of footwear on all facets of children's gait.…”
Section: Children's Footwear Effect On Gaitmentioning
confidence: 98%
“…The methods used in children’s footwear research both in their design and to explore their effects on the child mainly consisted of biomechanical and anthropometric studies, with a minority of studies considering the physiological and psychosocial effects. In consideration of typical development a number of biomechanical studies now exist which compare barefoot and shod conditions on children’s gait and other motor tasks [6, 12, 49, 158, 159]. The majority of these biomechanical studies were carried out in children of primary school age compared to the other age groupings.…”
Section: Discussionmentioning
confidence: 99%
“…The purchase of children's footwear is a common source of angst for parents and caregivers [5], with ill-fitting and poor choice of footwear often cited as the basis of foot-related issues as adults [6]. This angst can be heightened when children present with disability or developmental concerns, where specific footwear features may assist in achieving, improving or maintaining ambulation [7][8][9][10]. The lack of consistency in descriptors of footwear types and features can stymie both health professionals and parents as it is typically dependant on the individual retail centre to interpret prescribed or recommended inclusions.…”
Section: Introductionmentioning
confidence: 99%